2019
DOI: 10.1111/edt.12478
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the aetiological factors of dental trauma in children over time: An 18‐year retrospective study

Abstract: Background/Aim Dental trauma causes significant aesthetic, functional and psychosocial problems that often require emergency attention in children. The aim of this retrospective study was to assess the factors related to dental injuries in children. A secondary aim was to better understand how to improve the education given to children, parents and teachers in schools regarding dental trauma. Materials and methods Records of children who were referred to the Department of Pedodontics at Suleyman Demirel Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 30 publications
(90 reference statements)
4
24
0
8
Order By: Relevance
“…The main causes for dental trauma in children are falls and injuries sustained during play. These findings are supported by some previous studies in the literature (9,10,15,16,28,37).…”
Section: Discussionsupporting
confidence: 92%
“…The main causes for dental trauma in children are falls and injuries sustained during play. These findings are supported by some previous studies in the literature (9,10,15,16,28,37).…”
Section: Discussionsupporting
confidence: 92%
“…Globally, TDIs are the most common type of head and face injuries seen in childhood 10 . Several studies that have examined the etiology of traumatic dental injuries in childhood and adolescence have shown that falls and crashes that occur during physical activities and sporting activities are among the main reasons 20‐22 . Several studies have investigated traumatic dental injuries and found correlations of varying degrees between dental injuries resulting from falls and orofacial region anatomy (eg, increased overjet and short frenulum), anthropometric measures (eg, obesity), behavioral structure (eg, hyperactivity, peer bullying, sleeping disorders), and certain drugs (eg, methylphenidate) 23‐32 .…”
Section: Discussionmentioning
confidence: 99%
“…10 Several studies that have examined the etiology of traumatic dental injuries in childhood and adolescence have shown that falls and crashes that occur during physical activities and sporting activities are among the main reasons. [20][21][22] Several studies have investigated traumatic dental injuries and found correlations of varying degrees between dental injuries resulting from falls and orofacial region anatomy (eg, increased overjet and short frenulum), anthropometric measures (eg, obesity), behavioral structure (eg, hyperactivity, peer bullying, sleeping disorders), and certain drugs (eg, methylphenidate). [23][24][25][26][27][28][29][30][31][32] Although it is reasonable to suppose that children with visual impairments and decreased depth sensation are more susceptible to accidents and falls, the relationship between stereopsis and visual impairment and TDI have not previously been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Os TDA apresentam diversos fatores etiológicos, que podem envolver questões ambientais (parques inseguros) e individuais (aumento da protusão e overjet, déficit de atenção, hiperatividade, limitações físicas). Foi observado que os fatores etiológicos relacionados aos TDA em crianças permanecem os mesmos ao longo dos anos (Kirzioglu e Oz, 2019). Esses fatores etiológicos podem, também, estar muito relacionados à idade do paciente.…”
Section: Fatores Etiológicos E Predisponentesunclassified